Pengaruh Profitabilitas, Sales Growth, Beban Pajak Tangguhan, dan Capital Intensity terhadap Tax Avoidance - Eprilya Setyorini; Indah Rahayu Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to determine the effect of profitability, sales growth, deferred tax expense, and capital intensity on tax avoidance. The object of this study consists of manufacturing companies in the non-cyclicals sector listed on the Indonesia Stock Exchange (IDX) in the financial statements during the period from 2020 to 2023. The sampling technique in this study used purposive sampling method which resulted in a total sample of 67 companies. The analysis technique used is multiple linear regression analysis using SPSS version 22.0 software. The results of this study indicate that profitability, sales growth, and capital intensity have a negative and significant effect on tax avoidance, meanwhile deferred tax expense has no a significant effect on tax avoidance.